Ivo Starý. Issue 37 (2nd October 2018) - Unknown
Abstract: "The Starý group is focused on the development of new synthetic methodologies for the preparation of non‐trivial π‐electron systems." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800541 . Abstract : "The Starý group is focused on the development of new synthetic methodologies for the preparation of non‐trivial π‐electron systems." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800541 .